Implicature in Barrack Obama’s Presidential Candicacy Announcement Speech - Widya Fhitri; Rabbi Antaridha; Irsyad Shabri (Fakultas Sastra Universitas Ekasakti, 2020)
This research describes the use of implicatures. This study aims to see the message in Barack Obama's campaign speech. Furthermore, this study uses the implicature theory proposed by Grice and George Yule, the language function theory proposed by Geoffrey Leech and complemented by the ethnographic theory of communication by Dell Hymes. The data is taken from Barack Obama's utterances delivered in a campaign speech in Springfield, Illinois, USA on February 10, 2007. This research follows the research phase proposed by Sudaryanto. At the basic stage of the data, the writer used the listening method and the technique of listening to the free and speaking competently. At the analysis, the researcher used the pragmatic matching method. Based on the analysis, the researcher found forty-two implicatures contained in the thirty-eight teachings of Barack Obama in the campaign speech. In addition, each implicature has a different function and purpose.